Reversal of functional disorders by aspiration, expiration, and cough reflexes and their voluntary counterparts - Tomori, Zoltan (Frontiers in Physiology, 2012)
Agonal gasping provoked by asphyxia can save ~15% of mammals even from untreated ventricular fibrillation, but it fails to revive infants with sudden infant death syndrome. Our systematic study of airway reflexes in cats and other animals indicated that in addition to cough, there are 2 distinct airway reflexes that may contribute to auto-resuscitation. Gasp- and sniff-like spasmodic inspirations can be elicited by nasopharyngeal stimulation, strongly activating the brainstem generator for inspiration, which is also involved in the control of gasping. This “aspiration reflex” (AspR) is characterized by spasmodic inspiration without subsequent active expiration and can be elicited during agonal gasping, caused by brainstem trans-sections in cats. Stimulation of the larynx can activate the generator for expiration to evoke the expiration reflex, manifesting with prompt expiration without preceding inspiration. Stimulation of the oro-pharynx and lower airways provokes the cough reflex which results from activating of both generators. The powerful potential of the AspR resembling auto-resuscitation by gasping can influence the control mechanisms of vital functions, mediating reversal of various functional disorders. The AspR in cats interrupted hypoxic apnea, laryngo- and bronchospasm, apneusis and even transient asphyxic coma, and can normalize various hypo- and hyper-functional disorders. Introduction of a nasogastric catheter evoked similar spasmodic inspirations in premature infants and interrupted hiccough attacks in adults. Coughing on demand can prevent anaphylactic shock and resuscitate the pertinent subject. Sniff representing nasal inspiratory pressure and maximal inspiratory and expiratory pressures are voluntary counterparts of airway reflexes, and are useful for diagnosis and therapy of various cardio-respiratory and neuromuscular disorders.